A combination of valproic acid sodium salt, CHIR99021, E-616452, tranylcypromine, and 3-Deazaneplanocin A causes stem cell-like characteristics in cancer cells - Sha, Shuang (Oncotarget, 2017)
Many studies are based on the hypothesis that recurrence and drug resistance in lung carcinoma are due to a subpopulation of cancer stem-like cells (CSLCs) in solid tumors. Therefore it is crucial to screen for and recognize lung CSLCs. In this study, we stimulated non-small cell lung cancer (NSCLC) A549 cells to display stem cell-like characteristics using a combination of five small molecule compounds. The putative A549 stem cells activated an important CSLC marker, CD133 protein, as well multiple CSLC-related genes including ATP-binding cassette transporter G2 (ABCG2), C-X-C chemokine receptor type 4 (CXCR4), NESTIN, and BMI1. The A549 stem-like cells displayed resistance to the chemotherapeutic drugs etoposide and cisplatin, epithelial-to-mesenchymal transition properties, and increased protein expression levels of NOTCH1 and Hes Family bHLH Transcription Factor 1 (HES1). When A549 cells were pretreated with a NOTCH signaling pathway inhibitor before compound induction, expression of the NOTCH1 target gene HES1 was reduced. This demonstrated that the NOTCH signaling pathway in the putative A549 stem-like cells had been activated. Together, the results of our study showed that a combination of five small molecule agents could transform A549 cells into putative stem-like cells, and that these compounds could also elevate CD133 and ABCG2 protein expression levels in H460 cells. This study provides a convenient method for obtaining lung CSLCs, which may be an effective strategy for developing lung carcinoma treatments.